Study on the strength of diameter-reducing solder balls by shear and pull tests. Issue 4 (31st May 2019) - Yu, Kehang; Yang, Chen; Wang, Jun; Yu, Jiabo; Yang, Yi
Abstract : Purpose: The purpose of this paper is to study the variation of the mechanical strength and failure modes of solder balls with reducing diameters under conditions of multiple reflows. Design/methodology/approach: The solder balls with diameters from 250 to 760 µm were mounted on the copper-clad laminate by 1-5 reflows. The strength of the solder balls was tested by the single ball shear test and pull test, respectively. The failure modes of tested samples were identified by combing morphologies of fracture surfaces and force-displacement curves. The stresses were revealed and the failure explanations were assisted by the finite element analysis for the shear test of single solder ball. Findings: The average strength of a smaller solder ball (e.g. 250 µm in diameter) is higher than that of a larger one (e.g. 760 µm in diameter). The strength of smaller solder balls is more highly variable with multiple reflows than larger diameters balls, where the strength increased mostly with the number of reflows. According to load-displacement curves or fracture surface morphologies, the failure modes of solder ball in the shear and pull tests can be categorized into three kinds. Originality/value: The strength of solder balls will not deteriorate when the diameter of solder ball is decreased with a reflow, but a smaller solder ball has a higher failure risk after multiple reflows. The failure modes for shear and pull tests can be identified quickly by the combination of force-displacement curves and the morphologies of fracture surfaces.